EXPERIENCE OF USING ELECTRICAL TOMOGRAPHY, RADON SURVEY AND MICROSEISMIC SOUNDING IN SEARCH FOR PIPES CONTROLLED BY FAULT ZONES - K. Zh. Seminsky (Geodinamika i Tektonofizika, 2020)
The complex of geophysical methods was successfully applied in the Alakit-Markha kimberlite field of the Yakutsk diamondiferous province. A pipe was identified in the local forecast area specified within the field at the previous stage of prospecting. The studies using electric tomography (ET), radon survey (RS) and microseismic sounding (MS) covered an area of ≈1000⨯500 m. Based on the jointly processed ET and RS plan images and MS profiles, a tubular body was detected in the sedimentary cover. It is confined to a fault node and stands out among the host rocks by low electrical resistivity, increased soil radon concentrations and high spectral ratios of the horizontal and vertical components of microseisms. Its complex shape is manifested at the ground surface by two isometric structures (each being several hundred meters long), which jointly form a dike-like body at a depth of ≈40 m, as shown by the electrical tomography images. According to the MS data, its root part is detected to comprise one or two fractured narrow zones that are traceable to a depth of 2 km and below. The structure of the identified body and its chemical composition will be determined after exploratory drilling is complete. Today there are grounds to conclude that using ET, RS and MS methods jointly as a complex described in the article proved effective for identifying pipes controlled by fault zones in the sedimentary cover areas.